Contribuição ao estudo geográfico do Município de Nanuque- MG - Cerqueira Neto, Sebastião Pinheiro Gonçalves de (2001)
This research suggests the realization of a survey on the geographic aspects of Nanuque in the state of Minas Gerais, analyzing the physical elements, but without ignoring the human activities that have interfered with the natural cycle of terrestrial evolution. We have also tried to correct some mistaken conceptions that persisted of many years on the geography on the region, like its physical location inside the state, climate changes due to the decrease of the native vegetation, etc. Our research on the physical aspects of Nanuque and its surrounding area, combined with specific bibliographic references, rests on the theory of a stage of balance. The antrophic atuation through urbanization can be viewed throught the deforestation in the area, but the question of equilibrium still provokes much discussion amongst researchers who are pursuing an exact method of expressing and quantifying the environmental imbalance provoked by man. In this dissertation we have tried not just to repeat the conclusions made by other researchers, but to expand on the current body of work.